1989
DOI: 10.1177/003693308903400609
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Colonic Adenocarcinoma and Extragenital Malignant Mixed Mesodermal Tumour

Abstract: A synchronous occurrence of large bowel adenocarcinoma and extragenital malignant mixed mesodermal tumour (MMMT) is reported. This case represents the sixth extragenital MMMT reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…MMMT of peritoneal origin is much more rare. It was first reported by Ober and Black (1) in 1955, and the present case is only the 32nd to be reported worldwide (2−22) (Table 1). Almost all the patients were postmenopausal women, with the mean age being 68 years.…”
Section: Discussionsupporting
confidence: 56%
“…MMMT of peritoneal origin is much more rare. It was first reported by Ober and Black (1) in 1955, and the present case is only the 32nd to be reported worldwide (2−22) (Table 1). Almost all the patients were postmenopausal women, with the mean age being 68 years.…”
Section: Discussionsupporting
confidence: 56%
“…Primary peritoneal neoplasms composed of both malignant epithelial and stromal elements have variously been referred to as extragenital malignant mixed mesodermal tumors (1)(2)(3)(4)(5), malignant mixed müllerian tumors (6 -18), carcinosarcomas (19 -21) and mixed tumors of müllerian type (22)(23)(24). This lack of consistent terminology reflects both the rarity of these lesions, mostly described in single case reports, as well as the uncertainties concerning the histogenesis.…”
mentioning
confidence: 99%
“…MMMTs have also been associated with other primary tumors such as ovarian thecoma and serous adenocarcinoma [39, 40]. El-Jabbour et al reported a case of extragenital MMMT with a synchronous colonic adenocarcinoma [41]. …”
Section: Discussionmentioning
confidence: 99%